Enhancing Online Art Purchasing Decision using Virtual Try-On - Lee Mellon, Mckenna (My University, 2025)
This study aims to measure how Virtual Try-On (VTO) impacts customer satisfaction, attitudes, and purchasing decisions when buying art pieces in an online art gallery. VTO is the use of augmented reality utilizing virtual technology to superimpose objects on a person’s body or in their space. While VTO has been extensively studied in the fashion, makeup, and even furniture industries, it has yet to branch into the online art gallery sphere. This study addresses this knowledge gap by employing a quantitative survey of 370 art-enthusiastic, tech-savvy U.S. residents including clients of the Benesch Collection and respondents from Survey Monkey Audience. Building on established frameworks such as Technology Acceptance Model by Davis (1989), this survey captured potential customer’s satisfaction levels(SAT), attitudes (ATT), and overall purchasing decisions (PURD) using VTO during their shopping experience. The key findings of this study show that ease of use, perceived usefulness, and satisfaction levels all positively and directly increase the likelihood of a purchase. Pearson Correlation analysis shows a relationship between all three variables, ATT, SAT, and PURD, with the most correlated variables being SAT and ATT with a correlation score of .835 and the least correlated being PURD and ATT with a correlation score of .743. The Factor analysis also showed promising results that inform one of the survey’s overall validity. The results paint a picture showcasing how VTO can be used as a valuable tool in increasing customer satisfaction while encouraging positive attitudes towards the buying experience, thus limiting buyer apprehension and increasing purchasing decision likelihood. This study concludes with potential research to further this knowledge as well as limitations experienced throughout the research process. Research, such as continued qualitative studies in addition to this quantitative study, could greatly benefit tech developers as well as art professionals. Limitations include the size of the sample used and the use of additional material in the survey.
Keywords: Art Purchasing; Virtual Try-On; Campus Mexicali